Azolla (Azolla pinnata) as a Feed Ingredient in Broiler Ration - Basak, Biplob; Pramanik, Md. Ahsan Habib; Rahman, Muhammad Siddiqur; Tarafdar, Sharif Uddin; Roy, Bimol Chandra (International Journal of Poultry Science, 2001)
An experiment was conducted with 120 seven days old Vencobb commercial broiler chicks and continued up to 42 days of age to determine the feasibility of Azolla (Azolla pinnata) as a feed ingredient in broiler ration. The broilers are randomly allotted to four dietary treatments; T1 (control diet without Azolla meal), T2 (diet with 5% Azolla meal), T3 (diet with 10% Azolla meal) and T4 (diet with 15% Azolla meal) diets replacing sesame meal by Azolla meal. The composition of Azolla meal contained 25.78% crude protein, 15.71% crude fibre, 3.47% ether extract, 15.76% ash and 30.08% nitrogen free extract on the air-dry basis. Live weight, production number and protein efficiency were (P< 0.01) significantly improved at the level off 5% Azolla meal in broiler ration. Feed conversion ratio and energy efficiency were significantly (P< 0.01) improved in diet with 5% Azolla meal and control diet. Total cost Tk/kg broiler was significantly (P